2009
DOI: 10.1111/j.1600-0404.1974.tb02790.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dantrium®* on Spasticity in Multiple Sclerosis

Abstract: ABSTIIACTThe effect of a new peripherally acting @~n s c l e relaxant drug, Dantrium8, on spasticity was tested on 8 patients with a clear multiple sclerosis o r with a long-standing spastic paraparesis suggestive of multiple sclerosis. The effect was evaluated both with regular clinical examination and with elcctromyographic technique. The latter concerned a quantitative analysis of the patient's ability to voluntarily control fine neuromuseular activity both with and without the drug. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Treatment regimes are usually started at 25 mg once daily and increased gradually to a maximum of 400 mg divided into four doses. 53 Six studies were identified and three were excluded (open trial design 54 or MS patients representing less than half of the study sample 55;56 ).…”
Section: Dantrolenementioning
confidence: 99%
“…Treatment regimes are usually started at 25 mg once daily and increased gradually to a maximum of 400 mg divided into four doses. 53 Six studies were identified and three were excluded (open trial design 54 or MS patients representing less than half of the study sample 55;56 ).…”
Section: Dantrolenementioning
confidence: 99%
“…Several reports suggesting benefit of dantrolene sodium for the treatment of spasticity in MS are available, [65][66][67][68] but concern regarding its effects on the liver limit its use. Diazepam has been evaluated in an open-label crossover trial comparing it with dantrolene, 69 and a double-blinded trial comparing it with baclofen.…”
Section: Spasticitymentioning
confidence: 99%